Antibacterial properties of cinnamic and ferulic acids incorporated to starch and PLA monolayer and multilayer films. (June 2022) - Ordoñez, Ramón; Atarés, Lorena; Chiralt, Amparo
Abstract: Ferulic (F) and cinnamic (C) acids have shown great potential as antimicrobial additives in the development of active food packaging based on biodegradable polymers. However, previous studies on thermo-processed (TP) PLA matrices with 1 or 2%w/w of these compounds found no microbial growth inhibition due to their limited release. In this study, 2 or 3% of F and C were incorporated into starch and PLA films, using several strategies to promote their release from PLA, in order to obtain effective antimicrobial activity against E. coli or L. innocua . TP starch films with F or C presented antimicrobial capacity, C being more effective than F for both bacteria and L. innocua being more sensitive to both acids. However, PLA films obtained by three different techniques: TP, thermo-processing with the addition of plasticiser (TPP), and solvent casting did not exhibit antibacterial action. The incorporation of ferulic acid methyl ester into PLA films did not improve the antimicrobial effect, which suggested that the release limitation may not be related to chemical interactions with the end chain hydroxyl of PLA. Three-layer PLA assemblies, with an internal starch film loaded with F or C, were tested using TP-PLA, TPP-PLA, or cast-PLA films as contact layer. Diffusion of F and C through the PLA layer was highly hindered, regardless of the film preparation method. Therefore, no significant bacterial growth inhibition was observed for the three-layered films. The reduced molecular mobility in the PLA matrix was the limiting factor for the compound release and subsequent antimicrobial effect. Graphical abstract: Image 1